Phylogenetic Relationships of Trichoderma harzianum Based on the Sequence Analysis of the Internal Transcribed Spacer Region -1 of the rDNA - Siddiquee, Shafiquzzaman; Abdullah, Faridah; Tan, Soon Guan; Aziz, Emila Rohaza (INSInet Publications, 2007)
The goal of this study is to determine whether sequence analysis of internal transcribed spacer-1 region of the rDNA can be used to detect species level of Trichoderma harzianum. Internal transcribed spacer- 1 region (ITS 1) of the ribosomal DNA was amplified by polymerase chain reaction (PCR). To test the selected universal primers (ITS1 and ITS2) and conditions of the PCR, thirty-six of Malaysian Trichoderma isolates were used. The results of PCR product were positively performed purification. The PCR purification products were proved possible to amplify the ITS 1 region of all Trichoderma strains.The amplified DNA was sequenced and aligned against using ex-type strains sequencings from TrichoBLAST /GenBank and established Trichoderma taxonomy. Thirty-six isolates were positively identified as Trichoderma harzianum (32 strains) Trichoderma virens (3 strains) and Trichoderma longibrachiatum (1 strain) formed clearly defining phylogenetic analysis. T. virens and T. longibrachiatum which were used as an outgroup in these analyses. To this end, thus are proposed that the ITS-1 region sequences are used as the reference’s sequence for future study involving the identification and taxonomy of Trichoderma harzianum. Amplification of ITS 1 region of the rDNA has showed potential as a rapid technique for identifying Trichoderma harzianum successfully fungi in all cases.